Effect of the pipe material and burying depth on the thermal efficiency of earth-to-air heat exchangers. (September 2020) - Sakhri, Nasreddine; Menni, Younes; Ameur, Houari
Abstract: Aiming to provide the thermal comfort inside building houses in arid regions, an experimental investigation is performed regarding the effect of earth-to-air heat exchanger (EAHE) materials on the overall performances. A comparison is made between the efficiency of steel and PVC pipes. Furthermore, the variation of vertical soil temperature from the soil surface to 140 cm is determined. It is found from the comparison between EAHE made of PVC and steel that the pipe has a small effect on the outlet air temperature leaving the system. On the contrary, the pipe length has a big effect on the EAHE performance.